KEARIFAN LOKAL MASYARAKAT DESA ADAT SADE DALAM MENGHADAPI COVID-19 - Nur Arning Tengara Kasih; Renny Nurhasana (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
Local wisdom of indigenous village communities can be interpreted as ideas, principles of life, behavior, rules or norms, taboos, and punishments derived from the experience of hereditary ancestors, one of which is to deal with life problems, namely disasters. COVID-19 is a disaster that causes difficult conditions to arise in society because it has an impact on all aspects of life. Therefore, people should fight against not only COVID-19 virus attack, but also food scarcity, and hunger. This study refers to the theory of local knowledge suggested by Geertz (1983) stating that local knowledge is born from experiences that have been passed in dealing with disasters and is knowledge owned by local communities and managed locally, in which there is a "cultural" system that aims to unite members within it. With the local wisdom that Sade Village has as a traditional village, the people have their way of dealing with COVID-19. Therefore, the purpose of this study is to identify the local wisdom of the Sade Village community in dealing with COVID-19. This research uses a descriptive qualitative method and the data is analyzed using triangulation. This study finds that local wisdom is used as a living strategy by optimally utilizing natural capital to deal with unexpected disasters. The tradition of togetherness, cooperation, and mutual assistance carried out by the people of Sade Village has made no one infected with the COVID-19 virus and can face food shortages, so this tradition needs to be followed by an example to deal with COVID-19. Another finding is the need to preserve agricultural work as a way of survival.